Foaming ceramic as well as preparation method and application thereof
By using specific proportions of coal mine topsoil, feldspar waste ore, river sand and green silicon carbide manganese oxide combined with phosphorus slag in foamed ceramics, the problems of uneven foaming size and low strength of foamed ceramics are solved, and high-performance foamed ceramic production is achieved, meeting the requirements of sustainable development.
Patent Information
- Application Number
- CN202510064125.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
AI Technical Summary
The existing foamed ceramics produced by phosphorus slag have problems such as uneven foaming size and low product strength, which is difficult to meet the high-performance needs of building materials.
By combining the phosphorus slag with a mixture of coal mine topsoil, feldspar waste ore, river sand and green silicon carbide manganese oxide with a specific proportion, the chemical composition and liquid phase composition of the raw materials are adjusted to prepare foamed ceramics with uniform pore structure and high compressive strength.
The pore structure uniformity and compressive strength of foamed ceramics have been significantly improved, production costs have been reduced, and waste mineral resources have been effectively utilized, which meets the requirements of sustainable development.
Smart Images

Figure CN119822864A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foamed ceramic production, and in particular relates to a foamed ceramic and a preparation method and application thereof. Background Art
[0002] Phosphorus slag is water-quenched slag produced in the production process of yellow phosphorus. The output is relatively large, and these wastes are difficult to handle. If they are not used for a long time, they will cause very serious damage to the environment. At present, phosphorus slag is mostly used as an additional filler in the production of cement clinker, but some characteristics of the tailings limit its use in cement. In addition, since the aluminum and silicon content of phosphorus slag is relatively low, it is easy to soften and produce bubbles above 1200℃, so phosphorus slag is also difficult to be used in the preparation of ceramic wall and floor tiles and other materials.
[0003] Foamed ceramics are made of inorganic minerals such as mine tailings and industrial solid waste as the main raw materials, with special foaming agents added, and fired at high temperatures (1050℃~1220℃) in kilns. They are green, environmentally friendly, lightweight ceramic new building materials used for non-load-bearing internal and external partitions of buildings and architectural decoration. Foamed ceramics have the properties of light weight, fire resistance, sound insulation, chemical corrosion resistance, and aging resistance. However, due to the closed pores inside the foamed ceramics, the expansion of the internal pores under high temperature impact can easily lead to layered peeling or even bursting. At present, the production of foamed ceramics using phosphorus slag as the main material still has problems such as uneven foaming size and low product strength. Summary of the invention
[0004] The present invention aims to improve at least one technical problem in the background technology.
[0005] The first aspect of the present invention provides a foamed ceramic, comprising the following raw materials in parts by weight: 20-50 parts of phosphorus slag, 15-25 parts of coal mine topsoil, 3-8 parts of bentonite, 20-30 parts of feldspar waste ore, 10-15 parts of river sand, and 0.5-2 parts of foaming agent; the coal mine topsoil comprises, by mass percentage, 70%-75% of SiO2 and 13%-25% of A12O3; the feldspar waste ore comprises, by mass percentage, 3%-8% of K2O and 1%-4% of Na2O.
[0006] The present invention uses phosphorus slag as a main raw material to prepare foamed ceramics, realizes the recycling of phosphorus slag, effectively reduces the pollution of phosphorus slag to the environment, and utilizes the abandoned coal mine topsoil of the local lignite mine and the local feldspar waste ore, turning waste into treasure, and further reducing the production cost of the foamed ceramics; at the same time, the pore structure of the foamed ceramics is more uniform and the compressive strength is higher through the coal mine topsoil, feldspar waste ore, river sand and foaming agent in a specific proportion in the raw materials.
[0007] The physical phase composition of the phosphorus slag in the present invention is mainly cyclowollastonite, calcite, a small amount of lanceolite, etc. Among them, the thermal expansion coefficient of cyclowollastonite is relatively low. As a raw material for preparing foamed ceramics, it can reduce the thermal expansion coefficient of foamed ceramics, thereby improving the thermal shock resistance of foamed ceramics. In addition, the phosphorus slag contains calcium silicate, and the wollastonite crystal phase formed therefrom also helps to improve the strength of the foamed ceramics.
[0008] The SiO2 content in the chemical composition of phosphorus slag is relatively low, and the liquid phase is insufficiently formed during high-temperature firing, and the gas is easily dissipated, thereby reducing the porosity of the foamed ceramic. The river sand with a specific proportion in the present invention can effectively adjust the high-temperature liquid phase composition, so that uniform foamed ceramics with high porosity are formed during high-temperature firing; the present invention selects the local coal mine topsoil in Mile, which has high SiO2 and A12O3 contents and low ignition loss. The coal mine topsoil can form a liquid phase at a relatively low temperature, and the overall content of SiO2 and A12O3 in the raw materials can be adjusted by a specific proportion of coal mine topsoil, and the high-temperature liquid phase composition can be adjusted, thereby ultimately improving the strength of the foamed ceramic; the local feldspar waste ore contains K2O and Na2O, and the overall content of K2O and Na2O in the raw materials can be adjusted by a specific proportion of feldspar waste ore, so that the viscosity of the liquid phase formed during the high-temperature firing process is suitable for the formation and development of pores, thereby ultimately obtaining uniform foamed ceramics with a stable pore structure. The present invention makes the pores of the foamed ceramic product more uniform and more reasonably sized by using a specific proportion of coal mine topsoil, a specific proportion of feldspar waste ore and a specific proportion of river sand, and enables the foamed ceramic to have higher compressive strength.
[0009] Furthermore, the phosphorus slag includes, by mass percentage, SiO2 40%-45%, A12O3 3%-10%, Fe2O3 0.05%-0.5%, TiO2 0%-0.5%, CaO 35%-48%, MgO 3%-7%, K2O 0.5%-1.5%, Na2O 0%-1%, P2O5 0.5%-1.6%, and the rest is loss on ignition.
[0010] Furthermore, the mesh size of the phosphorus slag is 10 mesh to 40 mesh.
[0011] Furthermore, the foaming agent is a mixture of green silicon carbide and manganese oxide, wherein the green silicon carbide is 0.25 to 1 part by weight and the manganese oxide is 0.25 to 1 part by weight; the mesh size of the green silicon carbide is 800 to 1500 meshes.
[0012] The present invention selects a mixture of specific green silicon carbide and manganese oxide as a foaming agent, wherein the temperature at which green silicon carbide decomposes to generate CO2 and CO under the action of alkali metals and alkaline earth metals is above 950°C, which matches the temperature at which the powder produces a liquid phase, and the generated gas can be wrapped in the liquid phase to foam, while the manganese oxide can effectively provide oxygen elements to the green silicon carbide to ensure the stable foaming of the green silicon carbide. At the same time, the phosphorus slag can decompose to generate a certain amount of gas during the high-temperature sintering process, which plays the role of a loose channel, which is beneficial to the subsequent foaming of the green silicon carbide to form a uniform pore structure, and the river sand with a specific proportion in the raw material can form a sufficient liquid phase during the sintering process, thereby ensuring that the gas generated by the green silicon carbide during the sintering process has sufficient viscous resistance to form a pore structure.
[0013] The second aspect of the present invention provides a method for preparing the above-mentioned foamed ceramic, comprising the following steps:
[0014] The raw materials are mixed, granulated, aged and fired to obtain foamed ceramics.
[0015] Among them, the foaming agent is a mixture of green silicon carbide and manganese oxide; the sintering includes the following steps: a first heating, a second heating, a first heat preservation, a third heating, a second heat preservation, and a cooling in sequence; the target temperature of the first heating is 600°C, and the heating rate is 8°C / min to 12°C / min; the target temperature of the second heating is 900°C, and the heating rate is 5°C / min to 10°C / min; the temperature of the first heat preservation is 900°C, and the heat preservation time is 40min to 60min; the target temperature of the third heating is 1080°C to 1210°C, and the heating rate is 2°C / min to 5°C / min; the temperature of the second heat preservation is the target temperature of the third heating, and the heat preservation time is 45min to 90min; the cooling rate is 2°C / min to 4°C / min.
[0016] In the first heating, the main thing is the burnout of surface water and bound water of the raw materials, so a rapid heating method can be adopted; in the second heating and the first insulation, part of the raw materials begin to undergo oxidation and decomposition and physical and chemical reactions begin to occur to produce a small amount of low eutectic; in the third heating and the second insulation, the green silicon carbide reacts to form the overall pore structure of the foamed ceramic. It is necessary to reduce the heating rate and keep the temperature for a certain period of time to ensure that the green silicon carbide reacts completely to form a sufficient and uniform pore structure; the final cooling ensures that the foamed ceramic is evenly cooled to eliminate structural stress and avoid stress damage.
[0017] The raw materials are mixed by wet ball milling, granulated by spray drying, and aged for 24 hours.
[0018] Specifically, the raw materials are wet ball-milled for 6 to 8 hours to mix, and sieved to obtain slurry, and the slurry is spray-dried and granulated to obtain powder.
[0019] The third aspect of the present invention provides an application of the above-mentioned foamed ceramic in building materials.
[0020] The beneficial effects of the present invention are as follows: the present invention uses phosphorus slag as the main raw material, and combines it with coal mine topsoil, feldspar waste ore, river sand and foaming agent in specific proportions to prepare foamed ceramics with uniform pore structure and excellent compressive strength; the present invention makes full use of the local abandoned mineral resources in Mile, turning waste into treasure, which is in line with the national strategic requirements of circular economy and sustainable development, and is also an effective way to alleviate resource constraints and protect the ecological environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a photo of the foamed ceramic obtained in Example 1;
[0022] Figure 2 is a photograph of the foamed ceramic obtained in Example 2;
[0023] Figure 3 is a photograph of the foamed ceramic obtained in Example 3;
[0024] Figure 4 is a photograph of the foamed ceramic obtained in Example 4;
[0025] Figure 5 is a photograph of the foamed ceramic obtained in Example 5;
[0026] Figure 6 A photograph of the ceramic prepared in Comparative Example 1;
[0027] Figure 7 A photograph of the ceramic prepared in Comparative Example 2;
[0028] Figure 8 This is a photograph of the ceramic prepared in Comparative Example 3;
[0029] Fig. 9 This is a photo of Example 4 showing the application of foamed ceramics in building materials. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0031] The tests involved in the embodiments and comparative examples include:
[0032] Volume density test: The test method refers to GB / T 23451-2009. The equipment involved includes an electric blast drying oven, a balance, a 1mm steel ruler and a vernier caliper with a graduation value of 0.05mm. During the test, the surface density of the product is first measured and then multiplied by the thickness to convert it into volume density.
[0033] Compressive strength test: The test method refers to GB / T 23451-2009. The equipment involved includes a flexural strength testing machine, an electric blast drying oven, a balance, a 1mm steel ruler and a vernier caliper with a graduation value of 0.05mm.
[0034] Example 1
[0035] A foamed ceramic comprises the following raw materials in parts by weight: 38 parts of phosphorus slag (the mesh number of phosphorus slag is 10 mesh), 25 parts of coal mine topsoil, 5 parts of bentonite, 22 parts of waste ore feldspar, 10 parts of river sand, 0.25 parts of green silicon carbide (the mesh number of green silicon carbide is 800 mesh), and 0.25 parts of manganese oxide.
[0036] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0037] The preparation method is as follows:
[0038] The raw materials are wet-milled for 6 hours to obtain a slurry, which is then passed through a 100-mesh sieve and iron is removed. The slurry is then placed in a large slurry tank for stirring and homogenization for 12 hours and then spray-dried and granulated to obtain a powder (the moisture content of the spray-dried powder is controlled at 4% to 6%). The powder is passed through a 20-mesh sieve, the coarse particles are removed, and then the powder is transported to a sealed powder silo for aging for 24 hours for use;
[0039] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 11°C / min; continuing to heat to 900°C at a heating rate of 9°C / min, and keeping at 900°C for 40 minutes; continuing to heat to 1180°C at a heating rate of 3°C / min, and keeping at 1180°C for 70 minutes; finally cooling to below 150°C at a cooling rate of 3°C / min and leaving the kiln.
[0040] The foamed ceramic obtained in Example 1 has a uniform pore structure and its volume density is 512 kg / m3 , the compressive strength is 8.3MPa, and its photo is as follows Figure 1 shown.
[0041] Example 2
[0042] A foamed ceramic comprises the following raw materials in parts by weight: 36 parts of phosphorus slag (phosphorus slag mesh number is 20 mesh), 25 parts of coal mine topsoil, 5 parts of bentonite, 26 parts of feldspar waste ore, 8 parts of river sand, 0.25 parts of green silicon carbide (green silicon carbide mesh number is 1000 mesh), and 0.5 parts of manganese oxide.
[0043] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0044] The preparation method is as follows:
[0045] The raw materials are wet-milled for 7 hours to obtain a slurry, the slurry is passed through a 100-mesh sieve and iron is removed, the slurry is put into a large slurry tank for stirring and homogenization for 12 hours, and then spray-dried and granulated to obtain a powder (the spray-dried moisture content is controlled at 4% to 6.5%), the powder is passed through a 20-mesh sieve, the coarse particles are sieved out, and then the powder is transported to a sealed powder silo for aging for 24 hours for use;
[0046] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 10°C / min; continuing to heat to 900°C at a heating rate of 8°C / min, and keeping at 900°C for 50 minutes; continuing to heat to 1200°C at a heating rate of 4°C / min, and keeping at 1200°C for 80 minutes; finally cooling to below 150°C at a cooling rate of 4°C / min and leaving the kiln.
[0047] The foamed ceramic obtained in Example 2 has a uniform pore structure and its volume density is 492 kg / m 3 , the compressive strength is 7.9MPa, and its photo is as follows Figure 2 shown.
[0048] Example 3
[0049] A foamed ceramic comprises the following raw materials in parts by weight: 40 parts of phosphorus slag (the mesh number of phosphorus slag is 10 mesh), 25 parts of coal mine topsoil, 5 parts of bentonite, 25 parts of waste ore feldspar, 5 parts of river sand, 0.5 parts of green silicon carbide (the mesh number of green silicon carbide is 1200 mesh), and 0.25 parts of manganese oxide.
[0050] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0051] The preparation method is as follows:
[0052] The raw materials are wet-milled for 7.5 hours to obtain a slurry, which is passed through a 100-mesh sieve and iron is removed. The slurry is then placed in a large slurry tank for stirring and homogenization for 12 hours and then spray-dried and granulated to obtain a powder (the moisture content of the spray-dried material is controlled at 5% to 6.5%). The powder is passed through a 20-mesh sieve, the coarse particles are sieved out, and then the powder is transported to a sealed powder bin for aging for 24 hours for use; S1, the various formula materials of the foamed ceramic are weighed according to the ratio and added into the ball mill;
[0053] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 12°C / min; continuing to heat to 900°C at a heating rate of 6°C / min, and keeping at 900°C for 45 minutes; continuing to heat to 1168°C at a heating rate of 3.5°C / min, and keeping at 1168°C for 60 minutes; finally cooling to below 150°C at a cooling rate of 4°C / min and leaving the kiln.
[0054] The foamed ceramic obtained in Example 3 has a uniform pore structure and a bulk density of 502 kg / m 3 , the compressive strength is 8.9MPa, and the photo is as follows Figure 3 shown.
[0055] Example 4
[0056] A foamed ceramic comprises the following raw materials in parts by weight: 37 parts of phosphorus slag (the mesh number of phosphorus slag is 20 meshes), 25 parts of coal mine topsoil, 5 parts of bentonite, 25 parts of waste ore feldspar, 8 parts of river sand, 0.5 parts of green silicon carbide (the mesh number of green silicon carbide is 1500 meshes), and 0.5 parts of manganese oxide.
[0057] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0058] The preparation method is as follows:
[0059] The raw materials are wet-milled for 8 hours to obtain a slurry, the slurry is passed through a 100-mesh sieve and iron is removed, the slurry is put into a large slurry tank for stirring and homogenization for 12 hours, and then spray-dried and granulated to obtain a powder (the spray-dried moisture content is controlled at 4.5% to 6.5%), the powder is passed through a 20-mesh sieve, the coarse particles are sieved out, and then the powder is transported to a sealed powder silo for aging for 24 hours for use;
[0060] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 10°C / min; continuing to heat to 900°C at a heating rate of 4.5°C / min, and keeping at 900°C for 45 minutes; continuing to heat to 1175°C at a heating rate of 3°C / min, and keeping at 1175°C for 60 minutes; finally cooling to below 150°C at a cooling rate of 3.5°C / min and leaving the kiln.
[0061] S3. Apply the spray powder cloth into the multi-layer refractory mold filled with refractory wool and scrape it flat, put it into the tunnel kiln, and fire it according to the set firing curve. The highest firing temperature is 1175℃. The firing process is: room temperature ~ 600℃, use a heating rate of 10℃ / min; 600℃ ~ 900℃, use a heating rate of 4.5℃ / min, keep warm for 45min; 900℃ ~ 1175℃, use a heating rate of 3℃ / min, keep warm for 60min. From 1175℃ to room temperature, use a cooling rate of 3.5℃ until it cools to below 150℃ and leaves the kiln.
[0062] The foamed ceramic obtained in Example 4 has a uniform pore structure and a bulk density of 517 kg / m 3 , the compressive strength is 8.8MPa, and the photo is as follows Figure 4 shown.
[0063] Example 5
[0064] A foamed ceramic comprises the following raw materials in parts by weight: 30 parts of phosphorus slag (phosphorus slag mesh number is 20 mesh), 25 parts of coal mine topsoil, 5 parts of bentonite, 30 parts of waste ore feldspar, 10 parts of river sand, 0.5 parts of green silicon carbide (green silicon carbide mesh number is 1500 mesh), and 0.75 parts of manganese oxide.
[0065] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0066] The preparation method is as follows:
[0067] The raw materials are wet-milled for 7 hours to obtain a slurry, which is then passed through a 100-mesh sieve and iron is removed. The slurry is then placed in a large slurry tank for stirring and homogenization for 12 hours and then spray-dried and granulated to obtain a powder (the moisture content of the spray-dried material is controlled at 4% to 6%). The powder is passed through a 20-mesh sieve, the coarse particles are removed, and then the powder is transported to a sealed powder bin for aging for 24 hours for use; S1, the various formula materials of the foamed ceramic are weighed according to the ratio and added into a ball mill;
[0068] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 10°C / min; continuing to heat to 900°C at a heating rate of 8°C / min, and keeping at 900°C for 50 minutes; continuing to heat to 1185°C at a heating rate of 3.5°C / min, and keeping at 1185°C for 80 minutes; finally cooling to below 150°C at a cooling rate of 4°C / min and leaving the kiln.
[0069] The foamed ceramic obtained in Example 5 has a uniform pore structure and a bulk density of 577 kg / m 3 , the compressive strength is 10.8MPa, and the photo is as follows Figure 5 shown.
[0070] Comparative Example 1
[0071] A ceramic comprises the following raw materials in parts by weight: 55 parts of phosphorus slag (the mesh number of phosphorus slag is 20 meshes), 20 parts of coal mine topsoil, 5 parts of bentonite, 15 parts of waste ore feldspar, 5 parts of river sand, 0.5 parts of green silicon carbide (the mesh number of green silicon carbide is 1000 meshes), and 0.75 parts of manganese oxide.
[0072] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0073] The preparation method is as follows:
[0074] The raw materials are wet-milled for 7 hours to obtain a slurry, the slurry is passed through a 100-mesh sieve and iron is removed, the slurry is put into a large slurry tank for stirring and homogenization for 12 hours, and then spray-dried and granulated to obtain a powder (the spray-dried moisture is controlled at 4% to 6%), the powder is passed through a 20-mesh sieve, the coarse particles are sieved out, and then the powder is transported to a sealed powder silo for aging for 24 hours for use;
[0075] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 10°C / min; continuing to heat to 900°C at a heating rate of 8°C / min, and keeping at 900°C for 50 minutes; continuing to heat to 1185°C at a heating rate of 3°C / min, and keeping at 1185°C for 80 minutes; finally cooling to below 150°C at a cooling rate of 4°C / min and leaving the kiln.
[0076] The foamed ceramic prepared in Comparative Example 1 has a high whiteness, but has significantly larger cavities, and the distribution is very uneven. The pore structure strength is relatively low, and the whole is relatively brittle. The volume density is 465 kg / m 3 The compressive strength is low and has a large fluctuation range, which is 3 to 5 MPa. Figure 6 shown.
[0077] Comparative Example 2
[0078] A ceramic comprises the following raw materials in parts by weight: 30 parts of phosphorus slag (phosphorus slag mesh number is 20 mesh), 15 parts of coal mine topsoil, 15 parts of bentonite, 40 parts of waste ore feldspar, 10 parts of river sand, 0.5 parts of green silicon carbide (green silicon carbide mesh number is 1000 mesh), and 0.75 parts of manganese oxide.
[0079] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0080] The preparation method is as follows:
[0081] The raw materials are wet-milled for 7 hours to obtain a slurry, the slurry is passed through a 100-mesh sieve and iron is removed, the slurry is put into a large slurry tank for stirring and homogenization for 12 hours, and then spray-dried and granulated to obtain a powder (the spray-dried moisture is controlled at 4% to 6%), the powder is passed through a 20-mesh sieve, the coarse particles are sieved out, and then the powder is transported to a sealed powder silo for aging for 24 hours for use;
[0082] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 10°C / min; continuing to heat to 900°C at a heating rate of 8°C / min, and keeping at 900°C for 50 minutes; continuing to heat to 1185°C at a heating rate of 3°C / min, and keeping at 1185°C for 80 minutes; finally cooling to below 150°C at a cooling rate of 4°C / min and leaving the kiln.
[0083] The foamed ceramic obtained in Comparative Example 2 has a darker color, has significantly larger cavities, and is very unevenly distributed. The pore structure strength is low and the whole is relatively brittle. The volume density is 565 kg / m 3 The compressive strength fluctuates between 6 and 6.5 MPa. Figure 7 shown.
[0084] Comparative Example 3
[0085] A ceramic comprises the following raw materials in parts by weight: 15 parts of phosphorus slag (the mesh number of phosphorus slag is 20 meshes), 20 parts of coal mine topsoil, 5 parts of bentonite, 25 parts of waste ore feldspar, 35 parts of river sand, 0.5 parts of green silicon carbide (the mesh number of green silicon carbide is 1000 meshes), and 0.75 parts of manganese oxide.
[0086] Among them, the phosphorus slag includes, by mass percentage, SiO2 42.4%, A12O3 3.75%, Fe2O3 0.21%, TiO2 0.17%, CaO 46.28%, MgO 3.8%, K2O 0.64%, Na2O 0.42%, P2O5 1.53%, and the rest is loss on ignition; the coal mine topsoil includes, by mass percentage, SiO2 70.29%, A12O3 17.83%; the feldspar waste ore includes, by mass percentage, K2O 5.3%, Na2O 1.21%.
[0087] The preparation method is as follows:
[0088] The raw materials are wet-milled for 7 hours to obtain a slurry, the slurry is passed through a 100-mesh sieve and iron is removed, the slurry is put into a large slurry tank for stirring and homogenization for 12 hours, and then spray-dried and granulated to obtain a powder (the spray-dried moisture is controlled at 4% to 6%), the powder is passed through a 20-mesh sieve, the coarse particles are sieved out, and then the powder is transported to a sealed powder silo for aging for 24 hours for use;
[0089] The powder is applied to a multi-layer refractory mold filled with refractory wool and scraped flat, put into a tunnel kiln, and fired according to a set firing curve to obtain foamed ceramics, wherein the firing process is: heating to 600°C at a heating rate of 10°C / min; continuing to heat to 900°C at a heating rate of 8°C / min, and keeping at 900°C for 50 minutes; continuing to heat to 1185°C at a heating rate of 3°C / min, and keeping at 1185°C for 80 minutes; finally cooling to below 150°C at a cooling rate of 4°C / min and leaving the kiln.
[0090] The foamed ceramic obtained in Comparative Example 3 has good color, but the foaming is small, the pore structure strength is high, and it is not easy to process and carve. The volume density is 613kg / m 3 The compressive strength fluctuates between 11 and 12.5 MPa. Figure 8 shown.
[0091] The present invention uses phosphorus slag as the main basic raw material to produce foamed ceramics, and can produce foamed ceramic substrates with higher whiteness, and can also produce substrates of other relatively pure colors. The product has good foaming uniformity, is lightweight and low in density, has high strength, good physical and chemical properties, and is heat-insulating, sound-insulating, and fire-proof. It can be built or paved with the main body of the building through conventional bonding means (cement mortar or stone glue, tile glue, etc.), and the product can also be cut, drilled, and carved. The product is widely used in many application scenarios such as building partitions, exterior wall insulation, and building facade modeling.
[0092] The foamed ceramics prepared in Example 4 were applied to building materials (photos as shown in FIG. Fig. 9 and conduct performance testing, the results of which are shown in the following table.
[0093] Table 1 Performance test results
[0094]
[0095] It can be seen from Table 1 that the foamed ceramics of the present invention have good performance when used in building materials and meet the requirements of relevant standards.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A foamed ceramic, characterized in that: The raw materials include the following parts by weight: 20-50 parts of phosphorus slag, 15-25 parts of coal mine topsoil, 3-8 parts of bentonite, 20-30 parts of feldspar waste ore, 10-15 parts of river sand, and 0.5-2 parts of foaming agent; The coal mine topsoil comprises, by mass percentage, 70% to 75% of SiO2 and 13% to 25% of A12O3; the feldspar waste ore comprises, by mass percentage, 3% to 8% of K2O and 1% to 4% of Na2O.
2. The foamed ceramic according to claim 1, characterized in that: The phosphorus slag comprises, by mass percentage, 40% to 45% SiO2, 3% to 10% A12O3, 0.05% to 0.5% Fe2O3, 0% to 0.5% TiO2, 35% to 48% CaO, 3% to 7% MgO, 0.5% to 1.5% K2O, 0% to 1% Na2O, 0.5% to 1.6% P2O5, and the rest is loss on ignition.
3. The foamed ceramic according to claim 1, characterized in that: The mesh number of the phosphorus slag is 10 mesh to 40 mesh.
4. The foamed ceramic according to claim 1, characterized in that: The foaming agent is a mixture of green silicon carbide and manganese oxide.
5. The foamed ceramic according to claim 4, characterized in that: In parts by weight, the green silicon carbide is 0.25 to 1 part, and the manganese oxide is 0.25 to 1 part.
6. A method for preparing a foamed ceramic according to any one of claims 1 to 5, characterized in that: The following steps are involved: The raw materials are mixed, granulated, aged and fired to obtain the foamed ceramic.
7. The method for preparing foamed ceramics according to claim 6, characterized in that: The foaming agent is a mixture of green silicon carbide and manganese oxide; the sintering comprises the following steps: The first heating, the second heating, the first heat preservation, the third heating, the second heat preservation, and the cooling are performed in sequence; The target temperature of the first heating is 600°C, and the heating rate is 8°C / min to 12°C / min; the target temperature of the second heating is 900°C, and the heating rate is 5°C / min to 10°C / min; the temperature of the first insulation is 900°C, and the insulation time is 40min to 60min; the target temperature of the third heating is 1080°C to 1210°C, and the heating rate is 2°C / min to 5°C / min; the temperature of the second insulation is the target temperature of the third heating, and the insulation time is 45min to 90min; the cooling rate is 2°C / min to 4°C / min.
8. The method for preparing foamed ceramics according to claim 6, characterized in that: The raw material mixing method is wet ball milling; and / or the granulation method is spray drying.
9. The method for preparing foamed ceramics according to claim 6, characterized in that: The aging time is 24h.
10. Use of the foamed ceramic according to any one of claims 1 to 5 in building materials.
Citation Information
Patent Citations
Method for preparing yellow phosphorus scrap porous ceramic material
CN101289331A
Inorganic thermal insulation light aggregate prepared by phosphorous slag and preparation method thereof
CN101774776A
Preparation method of light-weight closed-pore ceramic heat insulating board
CN102838376A
Foamed ceramic preparation raw material and method based on coal mine stripping layer
CN112341246A
Foamed ceramic and preparation method thereof
CN113831109A